Intention to Use Islamic Fintech among MSMEs: Knowledge of Sharia Prohibition Approach - Jatnika, Muhammad Dzulfaqori; Friantoro, Dian; Muhammad, Mumuh; Iskandar, Iskandar; Alikhan, Liya Ur Rahman Liyakath (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2024)
The purpose of this study is to investigate the influential factors on behavioral intentions toward Islamic fintech use among Micro, Small and Medium Enterprises in Indonesia. The author adds a new research model about intention to use in the form of Technology Acceptance Model, Knowledge of Sharia Prohibition, Word of Mouth and Trust which has not been used in other studies. This research utilized a quantitative approach, an online survey was distributed to 350 MSMEs owners. The data collected from the participants were subjected to Structural Equations Modeling-Partial Least Squares (SEM-PLS) analysis, enabling a thorough examination of the variables under investigation. The results show that the variable of word of mouth and perceived ease of use have positive and significant impact on perceived usefulness. In addition, the variable of trust and perceived usefulness influence attitude significantly. This study also indicates that attitude affects intention to use Islamic fintech significantly. Then, the Attitude mediates the relationship between perceived usefulness and trust and Intention to use Islamic fintech. The findings of this study will be useful for policy makers and managers of Islamic fintech companies because it can help them find out the factors that drive intention to use Islamic fintech services.